PENGARUH BRAND IMAGE DAN ATRIBUT PRODUK TERHADAP KEPUTUSAN PEMBELIAN PADA HONDA SEKAWAN MOTOR JEMBER - Istifada, Agnes Dwi Arum; Wijayantini, Bayu; Winahyu, Pawestri (Relawan Jurnal Indonesia, 2022)
Brand image and product attributes are elements that reflect the overall product and service. Brand has an influence on consumer psychology, which means an image can influence consumers in buying products. Consumers tend to be attracted to products with a good image and product attributes that meet consumer expectations. This shows that Brand Image and Product Attributes affect purchasing decisions. This study aims to determine the effect of Brand Image and Product Attributes on Purchase Decisions at Honda Sekawan Motor Jember. The type of research used is quantitative research and data collection techniques using observation, interviews and questionnaires to 90 respondents with purposive sampling technique. The analytical tools used in this research are validity test, reliability test, classical assumption test, multiple linear regression analysis, T test, and R2 test. The results of testing the first hypothesis (H1) show that there is a significant influence between brand image on purchasing decisions with a significance level of 0.007 (p <0.05) and for the second hypothesis (H2) shows that there is a significant influence between product attributes on purchasing decisions. with a significance level of 0.000 (p<0.05). Thus it can be concluded that the variable brand image (X1) and product attributes (X2) together have an effect on purchasing decisions (Y) at Sekawan Motor Jember.